Soluble pectin acts as a particle stabilizer of tomato suspensions: The impact on tomato products rheological characterization. (March 2021) - Fei, Xing; Jones, Owen G.; Reuhs, Bradley L.; Campanella, Osvaldo H.
Abstract: We studied the flow behavior of reconstituted suspensions of tomato pulp dispersed in different pectin solutions to determine the effects of soluble pectin content and its chemical characteristics on the rheology of suspensions. Their rheological properties were characterized using the cone-plate and vane geometries and a Bostwick instrument. Pectin solutions exhibited Newtonian behavior and their viscosity increased with pectin concentration and its degree of methylation. The concentration of soluble pectin in the medium solution (serum) had a limited effect on viscosity whereas the physical characteristics of the tomato particles were a dominant factor. The average tomato particle size slightly increased with soluble pectin concentration and influenced viscosity. Increases in the soluble pectin concentration in serum increased interparticle interaction resulting in suspensions with larger flocculated particles that promoted the stability of the suspension. The vane geometry minimized slippage during testing and the measured viscosity was strongly correlated to Bostwick measurements. The cone-plate geometry induced significant phase separation and slippage at low serum pectin concentrations. Although the effect of soluble pectin on the viscosity of a suspension is minor, it does play a role in stabilizing suspensions by increasing the interparticle interaction and reducing serum separation. Highlights: Effect of soluble pectin on viscosity of concentrated tomato suspensions is small. Soluble pectin helps stabilization of tomato suspensions. The cone and plate geometry used in viscosity measurements promote artifacts. The vane geometry is more suitable for suspensions like tomato products. Results from vane geometry correlates with Bostwick results.